Influence of Spray Parameters on the Metallurgical and Functional Properties of HVOF WC Based Cermets Deposited onto Low Alloy Steel (Journal of Material Science and Technology Research, 2022)
Abstract: Tungsten carbide based spray coatings are widely used in industry for application requiring abrasion, sliding, fretting and erosion corrosion resistance. High velocity oxy-fuel (HVOF) flame spraying was used for producing high quality carbide composite coatings. In this study, a WC-CoCr and WC-CoCrNi powders were thermal sprayed using a HVOF process. The spray parameters were varied in order to investigate their influence on microstructure and mechanical properties of coatings. It is possible to produce homogeneous coating by controlling the flame temperature, the velocity of the gun transverse, the powder feed rate and the nature of the powders. The mechanical properties and the porosity rate could be optimized in order to improve the functional properties.